Student English Achievement and Their Learning Style: A Correlation Study on English Learners Exposure - Zulianti, Amanda; Asari, Slamet (English Language in Focus (ELIF), 2022)
The purpose of this study is to determine the relationship between students' learning styles and their English achievement. In this study, the researchers used quantitative methods and correlational research designs. The population of the study was students of Khaengsriphum School at Loei, Thailand. From the total population, 35 sixth-grade students were chosen as a sample. In collecting the data, students were given questionnaires and tests. The questionaire  that created by researcher was based on a learning style theory and used a Likert scale. In this study, the questionnaire addresses all learning styles, including visual, auditory, and tactile.  The Pearson Product Moment was then used to analyze the data from the test and to determine if there was a correlation between the two variables. For hypothesis testing, the researcher used SPSS version 25. Based on the results of categorizing students' learning styles through questionnaires, showed that 11 students (31%) preferred visual learning styles, 15 students (43%) preferred auditory learning styles, and nine students preferred tactile learning styles (26%). This indicated that Khaengsriphum School students tend to have auditory learning style. In addition to the questionnaire, the correlation test results revealed that students' learning styles had a significant relationship to their learning achievement, with a significance level of 0.00. The calculation results showed that students who referred to the visual learning style had  the highest correlation (0,908), followed by students who referred to the auditory learning style (0,827). Thus students who referred to tactile learning styles have the lowest correlation (0,823). In conclusion, although the visual learning style has the strongest correlation, the majority of students tended to prefer the auditory learning style during the learning process.